”Jo mere man ligner flertallet, jo lettere er det”: – en undersøgelse af minoritetsetniske studerendes trivsel på jordemoder- og sygeplejerskeuddannelsen - Nielsen, Annegrethe; Rasmussen, Annemette Vibeke; Pii, Kathrine Hoffmann (Tidsskrift for Professionsstudier, 2025)
Many ethnic minority students experience distress while studying. This affects the individual student’s quality of life, learning motivation, and educational achievement. Considering the recruitment crisis in the welfare professions and the desire for professionals to reflect the diversity of society, we investigate ethnic minority students’ academic and social well-being on the midwifery and nursing programmes. Well-being is understood from Ryan and Deci’s self-determination theory, which emphasizes the importance of experiencing autonomy, competence, and relatedness to be motivated. We conducted focus groups with students and teachers from the midwifery and nursing programmes and performed a deductive content analysis inspired by self-determination theory. The analysis shows that ethnic minority students experience a lack of relatedness to the broader community in the programmes, underestimation of their professional competencies and lack of recognition of autonomy by being perceived as a representative of an ethnic minority group. Ethnic minority students find that these issues are not addressed in the programmes, while teachers express uncertainty about handling ethnic diversity in the classroom. The results point to dynamics that threaten the well-being of ethnic minority students, which calls for action. We propose actions that address the elements that threaten wellbeing and potentially benefit all students.